Evaluation of Local Government Financial Performance from the Value for Money Perspective - Usman , Usman; Haeril , Haeril; Salida , Amrizal; Taufiq , Muhammad; Nur , Yustika (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study aims to evaluate the financial performance of local governments through the lens of the Value for Money (VfM) framework, which emphasizes the principles of economy, efficiency, and effectiveness in public sector spending. The growing demand for transparency and accountability in public administration necessitates a shift from traditional input-output financial measures to a more outcome-based evaluation approach. Using a quantitative research design, data were collected through structured questionnaires distributed to 135 respondents across selected local governments. Supplementary secondary data from official performance and audit reports were also analyzed. The findings indicate that all three VfM components—economy, efficiency, and effectiveness—have a significant and positive relationship with financial performance, with effectiveness showing the strongest influence. Multiple regression analysis revealed that the VfM framework accounts for a substantial portion of the variation in local government financial performance (Adjusted R² = 0.625). These results suggest that while cost control and resource utilization are important, achieving intended public service outcomes is the most critical factor in delivering value for money. This research contributes to the growing body of literature on public financial management by providing empirical evidence on the practical application of VfM principles at the local government level. It underscores the need for performance-based budgeting, robust monitoring systems, and institutional reforms to strengthen fiscal accountability and service delivery outcomes.